Operations management for dummies - Anderson, Mary Ann; Consumer Dummies Staff; Anderson, Edward G.; Parker, Geoffrey (Geoffrey G.) (For dummies, 2013)
Operations Management For Dummies serves as a resourceful aid for this difficult subject. Tracks to a typical course in operations management or operations strategy, and covers topics such as evaluating and measuring existing systems' performance and efficiency, materials management and product development, using tools like Six Sigma and Lean production, designing new, improved processes, and defining, planning, and controlling costs of projects.